Rule-based facial action units detection and dynamic analysis - Ujir, Hamimah; Hipiny, Irwandi; Awang Iskandar, D.N.F. (2016)
Most works in quantifying facial deformation are based on action units (AUs) provided by the Facial Action Coding System (FACS).AU is referring to a group of facial features that deform when a facial expression is shown.This paper presents a rule based approach to enumerate the AU which depends on certain facial features.This work only covers deformation of facial features based on posed Happy and the Sad expression obtained from the BU 4DFE database. According to the FACS rules lined in this work, an AU has more than one facial property that need to be observed.The intensity comparison and analysis on the AUs involved in Sad and Happy expression are presented.Additionally, dynamic analysis for AUs is studied to determine the temporal segment of expressions, i.e. duration of onset, apex and offset time.Our findings show that AU15, for sad expression, and AU12, for happy expression, show facial features deformation consistency for all properties during the expression period. However for AU1 and AU4, their properties’ intensity is different during the expression period.